Peculiarities of ZnSe dissolution in H₂O₂—HBr -ethylene glycol (oxalic acid) etchant compositions - Kravtsova, A.S.; Tomashyk, V.M.; Tomashyk, Z.F.; Stratiychuk, I.B.; Kuryk, A.O.; Kalytchuk, S.M.; Galkin, S.M. (Functional Materials, 2013)
The process of chemical treatment of undoped and doped ZnSe crystals surfaces by bromine emerging solutions has been investigated. The depending of dissolution rate on the etchants composition, their mixing and temperature has been studied. Concentration bounds of polishing solutions have been determined. The surface state after chemical etching has been established using electron microscopy and low temperature photoluminescence. The etchants compositions for semiconductors chemical polishing have been optimized. The comparative characteristics of two etching compositions H₂O₂—HBr —ethylene glycol and H₂O₂—HBr —oxalic acid have been shown to obtain high-quality polished surface of zinc selenide.